The perception of music feel between different musical sophistication levels - Wong, Kay Aik (2015)
The prevalence of music today has led to a myriad of musical preferences by different individuals, but these preferences are largely based on genres or styles of songs. Past researches have tried to find out people’s musical preference in terms of genres, but not scientific parameters of an audio stimulus, such as pitch or tempo. Music sophistication is a concept that seeks to quantify an individual’s propensity towards musical tasks; an individual with a higher musical sophistication would be able to perform musical tasks more effectively and efficiently than someone who has a lower musical sophistication. In 2010, a team of researchers from the United Kingdom distilled this concept further and came up with a novel measurement for musical sophistication, the Goldsmith Musical Sophistication Index (Gold-MSI). The Gold-MSI is found to be a reliable tool to measure one’s musical sophistication. In the same way where past researches attempted to find out if people who are more musically inclined will have different musical preference, this project seeks to find out the same way if one will react to the scientific parameters of pitch and tempo; hence the research question: “Will musical sophistication influence musical preference in terms of pitch and tempo?”To find out, a perceptual experiment was set up. Participants (n=21) listened to audio stimuli which are manipulated in different pitches and tempos, and then asked to rate how they feel for the stimuli. They filled out the Gold-MSI to find out their musical sophistication index. Results show that the question that whether musical sophistication influence musical preference is not conclusive, but the relatively high correlations between musical sophistication and pitch, and also tempo, encourages future researches to tap into this relationship.